STUDI TENTANG MINAT BACA MAHASISWA FAKULTAS ILMU PENDIDIKAN UNY - Hardianto, Deni (MAJALAH ILMIAH PEMBELAJARAN, 2011)
Reading books is one of the effective learning activities in acquiringscience and knowledge, but nowadays, the students reading interest isgetting lower. This research goals are: (1) describes the portrait of FIPUNY students, related to reading interests. (2) describes the FIP UNYstudents supporting and blocking factors in reading.This research uses the survey quantitative approach. The subjects are FIPUNY students. This research uses a questionnaires, observation, andinterviews for the data collection method, and being analyzed usingdescriptive analysis, tabulation of frequencies and percentages.From this research found: (1) the students reading interests, is generallyincluded in the low category, (2) the most students activities in campus isjust waiting in front of the class, only a small amount of students who usethe free time to read a book or to visit the library. (3)FIP students preferto read a popular, scientific book. They don’t interested in a scientificbook, because of the non attractive layout and design , (4) the studentstime to spent in reading the book is relatively low, less than 1 hour everyday, and in some cases, they never read except for the examinations, (5)the most students blocking factors in reading, comes from the studentitself, that shown in their low reading habits or hobbies.